Dopamine D1 receptor expression is bipolar cell type-specific in the mouse retina - Farshi, Pershang (J Comp Neurol, 2015)
In the retina, dopamine is a key molecule for daytime vision. Dopamine is released by retinal dopaminergic amacrine cells and transmits signaling either by conventional synaptic or by volume transmission. By means of volume transmission, dopamine modulates all layers of retinal neurons; however, it is not well understood how dopamine modulates visual signaling pathways in bipolar cells. Here, we analyzed Drd1a-tdTomato BAC transgenic mice and found that dopamine D1 receptor (D1R) is expressed in retinal bipolar cells in a type-dependent manner. Strong tdTomato fluorescence was detected in the inner nuclear layer and localized to type 1, 3b, and 4 OFF bipolar cells and type 5-2, XBC, 6, and 7 ON bipolar cells. In contrast, type 2, 3a, 5-1, 9, and rod bipolar cells did not express Drd1a–tdTomato. Other interneurons were also found to express tdTomato including horizontal cells and a subset (25%) of AII amacrine cells. Diverse visual processing pathways, such as color or motion-coded pathways are thought to be initiated in retinal bipolar cells. Our results indicate that dopamine sculpts bipolar cell performance in a type-dependent manner to facilitate daytime vision.